Role Performance, Acuity of Problems faced by School Assistant Principals at Jeresh Schools and Available Support Strategies from their point of view Caucasus - Kwakaza, Ferdous; Atari, Aref (Jadara Journal of Social Sciences, 2023)
This study aimed to investigate the role performance of assistant principals, identify the problems facing them, and the available strategies to support them from their point of view. The researchers applied the descriptive survey method and a questionnaire was used as a tool for data gathering. The sample consisted of (123) assistant principals at schools in Jerash Governorate. The study revealed that the estimates of both the role performance, the level of acuity of problems faced by the study sample members were high. The results also showed that the participants reported high levels of support strategies that are available to the assistant principal in Jerash governorate. The study concluded with discussion and recommendations.